Physico-Chemical parameters of Nizam sagar dam with respect to fish production Phytoplankton, Zooplankton - Totawar DV; Tamlurkar HL (International Journal of Life Sciences, 2017)
The main purpose of Nizam sagar dam is fish culture, irrigation, drinking, agriculture and also for domestic purpose. The present investigation deals with the physica-chemical parameters of Nizam sagar dam for fisheries management and culture of fish. The study was carried out for a period of twelve months during the academic year 2014. The parameters such as water temperature. pH, total alkalinity, dissolved oxygen and carbon dioxide were estimated. The pH shows alkaline trend in Nizam sagar dam. The water of Nizam sagar dam is found to be more suitable for fish culture.